Rapid establishment of a COVID-19 biobank in NHRI by National Biobank Consortium of Taiwan (2020)
By the request of the Minister of Health and Welfare, NHRI Biobank was assigned to establish a COVID-19 biobank in early Feb, 2020 to collect COVID-19 patients’ blood samples for Taiwan researchers and industries in an emergent way. It was set up in less than 3 weeks and quickly opened for application. By August 5, 2020, this COVID-19 biobank has collected 165 blood samples of 110 patients from more than 10 hospitals across north, middle and south part of Taiwan, including both COVID-19 (þ) and (-) pneumonia patients. This biobank can provide applicants with biosamples, such as serum, DNA and RNA, and also the clinical and genomic data, so as to accelerate the COVID-19 treatment and prevention research in Taiwan. This COID-19 biobank already received 15 applications. It has become the most important research resource for the COVID-19 pandemic in Taiwan, including new screening reagents, disease mechanism, the variable human responses and epidemic preventions. Since it is publicly available for both academic and industrial applicants.